Transient hypertrichosis with temporary tattooing in two siblings - Hülya Nazik; Feride Çoban Gül; Mehmet Kamil Mülayim; Perihan Öztürk; Serkan Kirik (Wolters Kluwer Medknow Publications, 2018)
Temporary tattooing with black henna is becoming increasingly popular among children and young adults. Complications are seen depending on additives added to henna for different purposes. Two sisters, aged 8 and 11, had a temporary tattoo. The tattoos began to disappear after 2 weeks. At the end of a month, pigmentation completely disappeared and hypertrichosis was observed on the site of the tattoo figures. There were no dermatitis findings in both cases. It was observed that hypertrichosis resolved spontaneously in two months. We think that it is meaningful to see the same effect by the same factor in two children with similar genetic background. In addition, knowing this benign complication related to temporary tattooing will prevent unnecessary invasive diagnostic and therapeutic interventions. Keywords: Child, Tatooing, Transient hypertrichosis